New concepts in freehand drawing education at architectural faculties - Makowska, Beata (EAAE Annual Conference Proceedings, 2025)
The paper discusses the attempt to adjust the syllabus for freehand drawing courses taught to students of landscape architecture at the Faculty of Architecture Cracow University of Technology in Poland and the International School of Engineering at Tianjin Chengjian University in China. This adjustment addresses the changing needs and future requirements in architectural practice. New concepts in freehand drawing education (less: routine, schematic thinking, fragmentary knowledge) were introduced in order to teach students the most important competences. New sketching topics are based on problem-solving skills (analytical and creative thinking, flexibility), the cross-sectional character of architectural education, critical thinking, awareness and individual responsibility, as well as elements of play. Sketching develops valuable skills that are extremely important for contemporary practice. They ensure fast decision-making, cognitive economy, independence from rules, incessant interaction with imagination, which are especially important at early stages of design. Therefore, this technique can still be a driving force of innovation, open- ing new perspectives in a drawing-based approach to the education of future architects.